2018
DOI: 10.3390/nano8040262
|View full text |Cite
|
Sign up to set email alerts
|

Thermocatalytic Behavior of Manganese (IV) Oxide as Nanoporous Material on the Dissociation of a Gas Mixture Containing Hydrogen Peroxide

Abstract: In this article, we present an overview on the thermocatalytic reaction of hydrogen peroxide (H2O2) gas on a manganese (IV) oxide (MnO2) catalytic structure. The principle of operation and manufacturing techniques are introduced for a calorimetric H2O2 gas sensor based on porous MnO2. Results from surface analyses by X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) of the catalytic material provide indication of the H2O2 dissociation reaction schemes. The correlation between theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…However, if the number of active sites was the only influencing factor, the 1Pb8Mn-WMon catalyst would exhibit a greater k value than 2Pb8Mn-WMon based on the TPR and H 2 chemisorption results; however, it was not. Thus, the other promotional effect of Pb 2+ , that is, transformation of Mn 2 O 3 into the MnO 2 phase, appearing in XRD, XPS and EDX patterns, was relevant . According to the XRD patterns, the minimum Mn 2 O 3 phase ratio was relevant to 1Pb8Mn-WMon, but its activity still appeared to be less than that of 1.5Pb8Mn-WMon.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, if the number of active sites was the only influencing factor, the 1Pb8Mn-WMon catalyst would exhibit a greater k value than 2Pb8Mn-WMon based on the TPR and H 2 chemisorption results; however, it was not. Thus, the other promotional effect of Pb 2+ , that is, transformation of Mn 2 O 3 into the MnO 2 phase, appearing in XRD, XPS and EDX patterns, was relevant . According to the XRD patterns, the minimum Mn 2 O 3 phase ratio was relevant to 1Pb8Mn-WMon, but its activity still appeared to be less than that of 1.5Pb8Mn-WMon.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, at the beginning of the reaction, due to the low concentration of radicals, the rate of the catalyst replenishment is rather low. To accelerate this, the presence of the optimum concentration of Mn 3+ species and accelerating the Mn 4+ /Mn 3+ redox transition in the MnO 2 catalyst are crucial . Thus, it can easily be concluded that the activity of MnO 2 depends on its crystalline form, average oxidation state (AOS), Mn 4+ /Mn 3+ redox transition ability, particle size, and surface area that are controllable during preparation of catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…This phase transformation was reported to occur at 500ºC because of the desorption of the lattice oxygen and thermal decomposition according to the following pathway [57,58]:…”
Section: Characterization Of the Ti/tio2 Nta-mnxoy Electrodesmentioning
confidence: 99%
“…Notably, the exothermic effect of the decomposition reaction of 50% hydrogen peroxide is used to launch underwater vehicles [ 61 , 62 ]. In this regard, the most effective catalysts are metals of the platinum group, Ag, Co, permanganates of alkali and alkaline-earth metals [ 63 ], manganese oxides, copper and chromium [ 64 , 65 , 66 ].…”
mentioning
confidence: 99%
“…It should be noted that the decomposition rate also increases with increasing pH. The decomposition of H 2 O 2 molecules in a gas mixture on a manganese (IV) oxide surface is considered in [ 64 ]. Thin films of alkaline earth metal oxides, for example, a MgO film on the surface of a molybdenum substrate, can also catalyze the decomposition of H 2 O 2 .…”
mentioning
confidence: 99%